PENGARUH ENJOYMENT, FLOW EXPERIENCE, TRUST TERHADAP INTENTION TO PLAY PADA GAME PLAYERUNKNOWN'S BATTLEGROUNDS (PUBG) MOBILE DI BENGKULU - Ivan Kurnia; Muhartini Salim; Sularsih Anggrawati; Aprima Widanti; Ilsya Hayadi (Jurnal Ilmiah Ekonomi Bisnis, 2019)
The purpose of this study were to determine the effect of enjoyment, flow experience, and trust toward the level of intention to play in online game  playerunknown's battlegrounds  (PUBG) mobile in Bengkulu. This study uses a quantitative approach using primary data obtained through online questionnaires. This study involved users of the game PUBG mobile in Bengkulu. The total sample in this study was 140 users of the game PUBG mobile in Bengkulu using the convenience sampling method. The data processing technique of this study used Statistical Package For Social Science (SPSS) software version 21.0. The analysis which is used including validity test, reliability test, and t test for hypothesis testing. The result revealed that; 1). Enjoyment has a positive and has a significant influence toward the level of intention to play; 2). Flow experience has a positive and has a significant influence toward the level of intention to play; 3). Trust has a positive and has a significant influence toward the level of intention to play felt by users of the PUBG mobile game in the  Bengkulu.